TINJAUAN TERHADAP TANGGUNG JAWAB YURIDIS KOMISI PEMILIHAN UMUM KABUPATEN KUTAI KARTANEGARA BEDASARKAN UNDANG-UNDANG NOMOR 15 TAHUN 2011 - Dalmasius Dalmasius (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACKThe next General Election is an Election called vital role in a Democracy. Especially Countries such as Indonesia is a Republic, As for the Institutions it serves to meet the three Principles of Democracy, namely : Popular Sovereignty, The Legitimacy Of Government and The Change Of Government on a regular basis and to the three Principles to ensure awake and implementing the ideals of independence and prevent certain interests in government bodies or substituted popular sovereignty became sovereign rulers of democratic elections is the expectation that every citizen with the right of people every Election can be united with both and in the general election no discrimination that resulted in the Destruction of Democratic Elections. When there is no Definite Election, Election Organizer in Indonesia is the Election Commission or the Abbreviated Commission. KPU is a National institution whose jurisdiction covers the entire territory of Indonesia then the Commission is an independent agency to do its job what it is free from the influence of those who want to destroy and inhibit the performance of the Commission.in carrying out their duties as Election, Organizers burden borne by what it is large because of fatigue in demand Elections quality makes running all Election Stages are the duties and obligations of the Commission, and the Commission guidance in performing tasks on RI law Number 15 of 2011 On General Election. Keyword :Tinjauan Yuridis